Chemical contamination can promote turnover diversity of benthic prokaryotic assemblages: The case study of the Bagnoli-Coroglio bay (southern Tyrrhenian Sea). (September 2020) - Tangherlini, M.; Corinaldesi, C.; Rastelli, E.; Musco, L.; Armiento, G.; Danovaro, R.; Dell'Anno, A.
Abstract: Chemical contamination of marine ecosystems represents a major concern for the detrimental consequences at different levels of biological organization. However, the impact of chronic contamination on the diversity and assemblage composition of benthic prokaryotes is still largely unknown, and this limits our understanding of the potential implications on ecosystem functioning. The Bagnoli-Coroglio bay (Gulf of Naples, Tyrrhenian Sea) is a typical example of coastal area heavily contaminated by metals and hydrocarbons, released for decades by industrial activities, which ceased at the beginning of nineties. In the present study we analyzed the abundance, diversity and assemblage composition of benthic prokaryotic assemblages at increasing distance from the historical source of contamination in relation to the heavy hydrocarbons (C > 12), polycyclic aromatic hydrocarbons (PAHs) and heavy metal concentrations in the sediments. Prokaryotic abundance in the sediments differed among sites, and was mostly driven by environmental factors rather than by contamination levels. Conversely, the richness of prokaryotic taxa was relatively high in all samples, was driven by contamination levels and decreased significantly with increasing contamination (15–38%). Moreover, our results indicate large variations in the composition of the benthic prokaryotic assemblages among sites, mostly explained by the different levels and types of chemical contaminants found in the sediments. Overall, our findings suggest that chemical contaminants, even after decades from the end of their release, can profoundly influence the richness and turnover diversity of the benthic prokaryotic assemblages, in turn promoting a high diversification of the benthic bacterial and archaeal assemblages by selecting those lineages more adapted to specific mixtures of different contaminants. Our results open new perspectives for understanding of the long-term effects of chemical contamination on the benthic prokaryotic assemblages and the ecological processes they mediate. Highlights: We analysed the influence of contamination on the benthic prokaryotic assemblages in the highly-polluted Bagnoli-Coroglio bay. The prokaryotic abundance in the sediments was driven by environmental factors rather than by contamination levels. The richness of prokaryotic taxa was high but slightly decreased (by 15% to 38%) with increasing contamination. We found large variations in prokaryotic taxa composition among sites, driven by the sediment contamination levels and types. Chemical contamination can affect the richness but promote the turnover (β-)diversity of the benthic prokaryotic assemblages.